Tracing the sources of 19th-century Russian realism: Ivan Panayev’s novella “Relatives” - Galon-Kurkowa, Krystyna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper concerns Ivan Panayev’s 1847 novella ‘Rodstvenniki’ (‘Relatives’). Scholars agree that this text in many respects foreshadows what was to become constitutive for 19th-century Russian realist prose, as embodied by the writings of Ivan Turgenev. What appears to be Panayev’s distinguishing feature is his hypothesis of meaning – however reserved the writer remains – in the fact of embedding the fate of his heroine in the prose of life.